2022
DOI: 10.1063/5.0096778
|View full text |Cite
|
Sign up to set email alerts
|

Multipurpose distributed dielectric-barrier-discharge plasma actuation: Icing sensing, anti-icing, and flow control in one

Abstract: Icing and stalling on the surfaces of aircraft wings endanger flight safety. In this work, the research object is a nanosecond pulsed dielectric-barrier-discharge plasma actuation unit with distributed layout, and the aerodynamic performance of aircraft wing surfaces under icing and stalling conditions is improved by changing the plasma-actuation electrical parameters. Actuated under low voltage and frequency, the unit acts as a sensor to judge icing according to the change in electrical parameters. Actuated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Recently, Abdollahzadeh et al [111] performed a parametric study to understand the effect of dielectric material, dielectric thickness, exposed electrode width, embedded electrode width, and gap on the performance of the plasma actuator as an ice sensor. Rodrigues et al [196] and Xie et al [197] have conducted further studies to investigate the suitability of DBD plasma actuators for multipurpose applications and demonstrated that these devices are capable of performing ice sensing, deicing, and flow control simultaneously.…”
Section: Ice Sensing By Dielectric Barrier Discharge Plasma Actuatorsmentioning
confidence: 99%
“…Recently, Abdollahzadeh et al [111] performed a parametric study to understand the effect of dielectric material, dielectric thickness, exposed electrode width, embedded electrode width, and gap on the performance of the plasma actuator as an ice sensor. Rodrigues et al [196] and Xie et al [197] have conducted further studies to investigate the suitability of DBD plasma actuators for multipurpose applications and demonstrated that these devices are capable of performing ice sensing, deicing, and flow control simultaneously.…”
Section: Ice Sensing By Dielectric Barrier Discharge Plasma Actuatorsmentioning
confidence: 99%
“…In addition, researchers revealed that plasma actuators produce considerable thermal effects during their operation, which can be used for icing mitigation [16][17][18][19]. Bearing this in mind, several researchers focused their studies on the operation of DBD plasma actuators for simultaneous active flow control and icing accumulation prevention [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, plasma anti/de-icing technology has become a research hotspot [14][15][16][17][18][19][20]. With in-depth research of dielectric-barrier discharge (DBD) plasma in the field of active flow control, its remarkable thermal properties have attracted attention in recent years and started to be widely used in plasma anti/deicing technology [21,22], which plays an important role in the field of plasma anti/de-icing. Researchers have conducted a significant amount of research in the field of anti/de-icing using DBD plasma and have achieved great results [15][16][17].…”
Section: Introductionmentioning
confidence: 99%